PENGARUH PEMBERIAN AIR SEDUHAN BAWANG PUTIH TERHADAP PENURUNAN TEKANAN DARAH PADA LANSIA PENDERITA HIPERTENSI DI WILAYAH KERJA PUSKESMAS PAMBOANG KABUPATEN MAJENE TAHUN 2018 - Immawanti Immawanti (Jurnal Kesehatan Marendeng, 2021)
Hypertension is often referred to as a dark killer (silent killer), because hypertension is a deadly disease without accompanied by symptoms first. One of the handling of blood pressure is using non-pharmacological therapy with herbs (the use of natural ingredients such as traditional medicinal plants such as garlic). Garlic containts the substance alisin and hydrogen sulfide as vasodilators. The aim of the study was to determine the effect of garlic steeping water on blood pressure reduction in elderly hypertensive patients for 3 consecutive days. This study was a Quasy Experiment study with the type of pre and post test without control design. The result of statistical analysis tests showed the influence before and after being given treatment of garlic steeping water to elderly hypertensive patients. That there is an effect of giving garlic steeping water to decrease blood pressure in elderly people with hypertension patients to use garlic steeping water as an alternative way to lower blood pressure.